Comparative evaluation of high-flow nasal cannula (HFNC) and conventional oxygen therapy (COT) in infants after non-cardiac surgery: Study protocol of a randomized controlled trial. - Diwei Zhang; Tianqing Gong; Qinghua Huang; Qianqian Zhang; Kai Liu; Jia Li; Hai Yu; Yu Cui (PLoS ONE)
Background Literature regarding the advantages of HFNC in infants for ensuring oxygen supply after non-cardiac surgery is insufficient. The purpose of our study is to compare COT vs. HFNC on postoperative outcomes in infants undergoing non-cardiac surgery. We hypothesize that prophylactic use of HFNC after non-cardiac surgery in infants would reduce the incidence of post-anesthesia hypoxemia and could also be adapted as first-line oxygen therapy after non-cardiac surgery. Methods This is a superior, single-blind, randomized controlled study. A total of 394 infants undergoing general anesthesia will be randomly assigned to accept COT or HFNC in a 1:1 ratio. The primary outcome is the rate of desaturation post-extubation. Secondary outcomes include the rate of mild upper airway obstruction, the rate of severe respiratory depression, the rate of transfer to PICU, duration of oxygen therapy, length of PACU stay, the time to reach full enteral feeding, and postoperative adverse events, including nasal injury, agitation, vomiting, and unplanned secondary surgery related to the initial surgery. Discussion This is the first randomized controlled trial to explore the advantages of HFNC in infants to ensure oxygen supply after non-cardiac surgery. If favorable evidence is obtained, HFNC could be adopted as first-line oxygen therapy for infants following non-cardiac surgery. Trial registration The trial was registered at https://www.chictr.org.cn (Registration number: ChiCTR2400081600, Date: March 6, 2024).